Cross-Border Integration of Renewable Energy Systems Experiences, Impacts, and Drivers - Anbumozhi, Venkatachalam; Bhupendra, Kumar Singh (Taylor & Francis, 2024)
Cross-border energy trade and integration of renewable energy have become significant for countries and regions to meet demands, minimize costs, and foster socio-economic and climate stability in the dynamic and unstable energy market. This book explores different models of global energy trade between regions and their benefits and challenges with a special focus on India's Northeast region. Countries in South and Southeast Asia are endowed with abundant renewable energy resources. This book examines the energy mix of the countries such as India, Myanmar, Thailand, Bangladesh, and Bhutan among others and their efforts to achieve more integrated markets and renewable energy integration in the region. It highlights the potential of Northeast India given its rich natural resources and strategic location to harness the potential cross-border energy trade with ASEAN countries. The volume provides analytical perspectives on drivers, constraints, opportunities and barriers, as well as measures that countries could take to address institutional, financial, policy, and governance issues to minimize the total costs of energy security and maximize the social-economic benefits for people in these regions. It identifies the necessary conditions - grid flexibility, policy, market, and regulatory solutions for clean energy trade - and contributes to growth of low-carbon development as well as policy making by focusing on renewable energy integration across borders. This volume will be of interest to students and researchers of energy and climate studies, environmental politics, trade, and economics and international relations. This book is freely available as a downloadable Open Access PDF at www.taylorfrancis.com under a Creative Commons (CC-BY-NC-ND) 4.0 license.